Dendrobium officinale alleviates high-fat diet-induced nonalcoholic steatohepatitis by modulating gut microbiota - Tian, Gege; Wang, Wei; Xia, Enrui; Chen, Wenhui; Zhang, Shunzhen (Frontiers in Cellular and Infection Microbiology, 2023)
The gut microbiota and liver inflammation play an important role in the development of nonalcoholic steatohepatitis (NASH). This study investigated the preventive effect of Dendrobium officinale (DO), including whether its effect was related to the gut microbiota, intestinal permeability and liver inflammation. A NASH model was established in rats using a high-fat diet (HFD) and gavage with different doses of DO or Atorvastatin Calcium (AT) for 10 weeks. Body weight and body mass index along with liver appearance, weight, index, pathology, and biochemistry were measured to assess the preventive effects of DO on NASH rats. Changes in the gut microbiota were analyzed by 16S rRNA sequencing, and intestinal permeability and liver inflammation were determined to explore the mechanism by which DO treatment prevented NASH. Pathological and biochemical indexes showed that DO was able to protect rats against HFD-induced hepatic steatosis and inflammation. Results of 16S rRNA sequencing showed that Proteobacteria, Romboutsia, Turicibacter, Lachnoclostridium, Blautia, Ruminococcus_torques_group, Sutterella, Escherichia-Shigella, Prevotella, Alistipes, and Lactobacillus_acidophilus differed significantly at the phylum, genus, and species levels. DO treatment modulated the diversity, richness, and evenness of gut microbiota, downregulated the abundance of the Gram-negative bacteria Proteobacteria, Sutterella, and Escherichia-Shigella, and reduced gut-derived lipopolysaccharide (LPS) levels. DO also restored expression of the tight junction proteins, zona occludens-1 (ZO-1), claudin-1, and occludin in the intestine and ameliorated the increased intestinal permeability caused by HFD, gut microbiota such as Turicibacter, Ruminococcus, Escherichia-Shigella, and Sutterella, and LPS. Lower intestinal permeability reduced LPS delivery to the liver, thus inhibiting TLR4 expression and nuclear factor-kappaB (NF-κB) nuclear translocation, improving liver inflammation. These results suggest that DO may alleviate NASH by regulating the gut microbiota, intestinal permeability, and liver Inflammation.